The Effects of Induced Emotions on Leading-by-Example - Michalis Drouvelis; Zeyu Qiu (CESifo GmbH, 2024)
This paper investigates the effects of induced emotions on leading-by example. Using an online sample of more than 1,000 participants, we observe behavior in a one-shot sequential voluntary contribution mechanism game where leaders and followers are induced to be either happy or angry. Our findings show that angry leaders contribute less than happy leaders. The same effect is observed when considering followers' behavior. Crucially, controlling for leaders' contributions, the mood effects on followers' behavior disappear, implying that it is sufficient to induce emotions only on leaders in order to affect followers' behaviour. Our findings further highlight the role of emotions as a causal force, suggesting that negative changes in well-being can bring about adverse effects on team cooperation.
Keywords: C92; D07; H41; 330; induced emotions; anger; happiness; contribution; leading-by-example